Skoobs : a bookshop experience with a difference - Gaylard, Alison; Cohn, Sid ([London] : SAGE, 2016)
When Marisa Torrani took a brief moment to relax in one of the elegant armchairs in her book emporium, Skoobs Theatre of Books, she drank in the scene with satisfaction. It was 6pm on a Friday in June 2012, 18 months since Skoobs had opened in the Montecasino entertainment and gaming complex, just north of Johannesburg. The store was filling up with customers and, as she watched, she couldn't help wondering what it was, exactly, that drew people to Skoobs. She had often thought about opening more stores, but would a Skoobs store survive beyond the alluring walls of Montecasino? This book reveals all.
Originally Published in: Gaylard, A., & Cohn, S. (2012). Skoobs: A Bookshop Experience with a Difference. WBS-2012-9. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Skoobs Theatre of Books (Firm); Booksellers and bookselling -- Case studies